2016
DOI: 10.1177/0008429816643115
|View full text |Cite
|
Sign up to set email alerts
|

Christian and Muslim Immigrant Women in the Canadian Maritimes

Abstract: This article details the strengths and vulnerabilities that Christian and Muslim immigrant women bring to situations of domestic violence in the Canadian Maritimes. An intersectional theoretical framework grounds the analysis of qualitative data collected from 89 Christian and Muslim women from 27 countries of origin who arrived in the region ten years prior to the field work. Their strengths include high levels of education, experiences of overcoming adversity, the ability to act strategically, and the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Otro aspecto del estudio indica que las puntuaciones altas de autoestima se correlacionan con menores puntuaciones de dependencia emocional. Estos resultados concuerdan con otros estudios, pues afirman que la dependencia emocional en mujeres tiene una asociación negativa con la autoestima (Henderson & Cunningham, 1993), este comportamientos de riesgo se debe a la dificultad de regular sus emociones (Weiss et al, 2018), responsabilidades con la unidad familiar (Holtmann, 2016), miedo al abuso y dependencia económica (McGrane et al, 2016). No obstante, algunos estudios indican que la relación entre baja autoestima y dependencia emocional en varones también es significativa, y que al tener una deficiencia percibida de amor violenta a su pareja (Kesner et al, 1997).…”
Section: Discussionunclassified
“…Otro aspecto del estudio indica que las puntuaciones altas de autoestima se correlacionan con menores puntuaciones de dependencia emocional. Estos resultados concuerdan con otros estudios, pues afirman que la dependencia emocional en mujeres tiene una asociación negativa con la autoestima (Henderson & Cunningham, 1993), este comportamientos de riesgo se debe a la dificultad de regular sus emociones (Weiss et al, 2018), responsabilidades con la unidad familiar (Holtmann, 2016), miedo al abuso y dependencia económica (McGrane et al, 2016). No obstante, algunos estudios indican que la relación entre baja autoestima y dependencia emocional en varones también es significativa, y que al tener una deficiencia percibida de amor violenta a su pareja (Kesner et al, 1997).…”
Section: Discussionunclassified
“…Many participants criticised and blamed other Afghan women for perpetuating gender stereotypes and particularly noted how their mothers imposed gender roles on them and other female members of the family. Likewise, Holtmann (2016) found that Afghan mothers might feel responsible for maintaining their family’s reputation and integrity; one aspect of this was the expectation that they brought up Afghan daughters who would maintain family and community obligations. Also, in another Muslim majority country, Marshall and Furr (2010) found that Turkish mothers were expected to endure oppression and violence and therefore sacrifice themselves and teach their daughters to do the same for the sake of family integrity.…”
Section: Discussionmentioning
confidence: 99%
“…The process of acculturation might entail an opportunity for women to liberate themselves from conservative gender roles (Harris et al, 2005). Thus, some researchers investigating the transformation of gender roles found that migrant women were more likely than men to change as they moved away from stereotypes and traditional roles (DeBiaggi, 2002;Holtmann, 2016;Moghissi et al, 2009). For instance, Moghissi et al (2009) found women were more likely than men to change in a host country that offered women more freedom and autonomy.…”
Section: Afghan Women and Gender Rolesmentioning
confidence: 99%
“…A belief system that condemns violence and oppression, and reinforces justice and liberation from abuse can increase a woman's willingness to seek help and promote healing following IPV trauma. Conversely, belief systems that blame survivors, support abusers, and compromise the safety of women and children in the name of family cohesiveness create additional trauma, and inflict secondary wounds, the "secondary victimization" (Hassouneh-Phillips, 2003;Holtmann, 2016). Hassouneh-Phillips (2003) explored the role of spirituality in the lives of Muslim women IPV survivors.…”
Section: Faith and Religious Beliefmentioning
confidence: 99%
“…Although diverse scholarly work focusing on the lived experiences of women survivors of IPV is crucial, it is also risky since it can be used to reinforce stereotypes held by members of the dominant group and further marginalize and isolate them (Holtmann, 2016;Sokoloff & Dupont, 2005). To decrease the risk for attribution of blame for IPV onto diverse cultures, researchers should reject the simplistic analysis of the role of culture in IPV.…”
Section: Implications For Research and Practicementioning
confidence: 99%